Food processing technology : principles and practice - Fellows, P. 1953- (CRC Press ; Woodhead Pub., 2000)
This book is split into five parts in which unit operations are grouped according to the nature of the heat transfer that takes place. Each chapter describes the theoretical and practical aspects of the unit operation including the formula required for calculation of processing parameters, sample problems, and the effects on sensory characteristics and nutritional properties of selected foods.
Keywords: Food industry and trade.; elektronické knihy; electronic books